Pengaruh Implementasi Project-Based Learning Berbasis Praktikum Sederhana Terhadap Hasil Belajar Kognitif Mata Pelajaran Biologi Pada Siswa Kelas XI SMA Negeri 1 Bongan - Siti Maria Mawar Dinata; Masitah Masitah; Akhmad Akhmad; Suparno Putera Makkadafi; Oktavianus Tae B.N (PendIPA Journal of Science Education, 2026)
Biology learning equipped with practicum can help students develop a further way of thinking. Based on the results of observations at SMA Negeri 1 Bongan, it is known that Biology activities have not been carried out optimally due to the limited facilities and infrastructure in the school. This study aims to determine the effect of the implementation of Project-Based Learning (PjBL) model based on simple practicum on the cognitive learning outcomes of Biology subjects in grade XI students of SMA Negeri 1 Bongan. This study uses a quantitative approach with the Quasi Experimental Design method and the Pre-test–Post-test Non-Equivalent Control Group Design design. The research sample consisted of 40 students divided into an experimental class and a control class, each totaling 20 students, with a sampling technique using purposive sampling. Data collection was carried out through cognitive learning outcome tests in the form of Pre-test and Post-test. Data analysis included the Shapiro-Wilk normality test, the Levene's Test homogeneity test, the N-Gain test, and the hypothesis test using the Mann-Whitney U Test. The results showed that the average Pre-test score of the  experimental class was 50.5 and the control class was 49, while the average Post-test score of the  experimental class was 82.75 and the control class was 77.5. The results of the N-Gain calculation showed that the experimental class obtained an average score of 0.67 and the control class 0.56, both of which were in the medium category. The results of the Mann-Whitney test on the Post-test data obtained a significance value (Sig. 2-tailed) of 0.028 < 0.05. Thus, it can be concluded that the implementation of Project-Based Learning based on simple practicum has a significant effect on the cognitive learning outcomes of Biology subjects in grade XI students of SMA Negeri 1 Bongan.